The Role of University Integration in Overcoming the Gap between Education Results and Real Needs of Labour Market - M. Shaheen (Вестник Российского экономического университета имени Г. В. Плеханова, 2023)
The article discusses the topic of overcoming the gap between results of professional education and actual needs of labour market in the current situation and the role of universities in the problem solution. Due to the fact that professional education provides students with a lot of important and fundamental knowledge in a certain sphere, but labour market needs change faster than the basic curriculum a gap turns up between education programs and requirements advanced to workers. As a result we can observe a situation when a qualified specialist possesses plenty of theoretical knowledge, but few practical skills necessary for work. It is an important and acute challenge for the education sphere, labour market and in the long run for society in general. The article studies key notions connected with interaction between labour market and education, proposes possible ways to cut the gap between education results and real needs of labour market and highlights potential barriers that can hinder this process. The author provides concrete examples of successful solution of the problem within the frames of implementing various partner programs of business and education both in Russia and abroad.